INSTA-GIRLHOOD: SELFIES AS AUTO-PERFORMATIVE RESPONSES TO SEXISM AND MISOGYNY (Journal of Contemporary Philology, 2022)
In this essay, I attend to the affective aesthetic dimensions of feminist art projects which critically engage with the trope of the Insta-girl in an attempt to raise issues about the cultural constructions of girlhood on social media and in “real life.” With the help of two case studies – Noa Jansma’s Dear Catcallers and Amalia Ulman’s Excellences & Perfections, I will discuss the production and consumption of a particular type of Insta-girl which appeal to audiences via modes of fetishization and abjection. Jansma’s work consists of selfies she took with random men who catcalled her. The documentary character of her project supports her project’s aim to record the nature, extent and frequency of catcalling she experienced. In turn, Amalia Ulman’s Excellences & Perfections critiques the construction, circulation and consumption of the trope of the Insta-girl, a postfeminist, late-capitalist figure characterized by her “oversharing” of intimate details about her everyday life. Both artists’ auto-performative responses to sexist and misogynistic tropes in social media impel audiences to question late-capitalist and neoliberal constructions of “girl-hood.”
Keywords: Insta-girl; #MeToo life writing; affect; Noa Jansma; Amalia Ulman